Sulfured FeMo carbides and nitrides catalysts upgrade extra heavy crude oil quality - Villasana, Yanet (2024)
In the context of the energy transition scenario, effective sulfur management is crucial. Enhancing the quality of extra heavy crude oil (EHCO) through catalytic processes, specifically hydrotreatment, is essential for reducing pollutant emissions like SOx into the atmosphere. Traditional hydrotreatment, utilizing MoS2-based catalysts typically on Al2O3 support, faces challenges with EHCO due to its elevated S and N content, which hampers catalyst efficiency. Metal carbides and nitrides exhibit promising electronic structures that confer resistance to deactivation in the presence of heteroatoms. This study compares the catalytic performances of Fe-promoted Mo sulfides, carbides, and nitrides (FeMoS(C,N)) in the thiophene hydrodesulfurization (HDS) reaction, serving as a model molecule for sulfur removal. Subsequently, we investigate the upgrading of a Venezuelan EHCO in terms of pollutant reduction, API gravity, and feedstock aromaticity. Catalysts were prepared from oxide precursors, varying the (Fe/(Fe+Mo)) atomic ratios (x = 0.00, 0.10, 0.33, 0.50, and 1.00), employing a temperature-programmed reaction protocol. Catalytic upgrading of EHCO was conducted in a stirred batch reactor, and the results were compared with a commercial CoMo-based catalyst. FeMoC(N) outperformed the commercial catalyst in sulfur removal. The elemental composition and nitrogen content of the feed remained constant; however, the sulfur content of asphaltenes decreased. Furthermore, the API gravity of crude oil increased when employing FeMoS and FeMoN catalysts, except with FeMoC, possibly linked to dealkylation reactions and the enrichment of lighter fractions with alkanes. FeMoN increased asphaltene aromaticity, while FeMoC decreased it. These results highlight the promise of FeMoC(N) as catalysts for HDS and upgrading heavy feedstocks.